Improved mechanical properties of multi-layered PTFE composites through hybridisation. (17th April 2023) - Bandaru, Aswani Kumar; Khan, Ashraf Nawaz; Durmaz, Tayfun; Alagirusamy, Ramasamy; O'Higgins, Ronan M.
Highlights: Novel PTFE composites with glass, aramid and metal mesh. Hybridisation enhanced interlaminar shear and flexural properties. Low velocity impact properties were improved while containing lightweight. Features of reinforcements were exploited to achieve optimized mechanical performance. Abstract: The current study demonstrates the utility of thermoplastic polytetrafluoroethylene (PTFE) composites for automotive, biomedical, electrical, food processing, civil engineering, tribology, and aerospace industries, etc. The PTFE composites reinforced with glass (G), aramid (A), a stainless-steel metal mesh (MM), and their combination were manufactured using an autoclave. The average fibre volume fraction of the composites was maintained at ∼52%. The performance of monolithic and hybrid composites was evaluated in terms of tensile, flexural, interlaminar shear strength (ILSS), and low-velocity impact (LVI). According to the experimental results, the monolithic G composites exhibited the highest tensile strength (134 MPa), while the hybrid G/MM composites showed the highest tensile modulus (3.8GPa). In flexural characteristics, hybrid MM/A (MM on the top) composites revealed superior flexural strength (76 MPa), whereas monolithic A composites showed excellent flexural modulus (6.5GPa) among all. The LVI performance was evaluated at three different energy levels (5 J, 10 J and 15 J) in terms of peak force, energy absorption, and peak deformation and compared. This study shows the positive influence of hybridisation, which signifies the utility of the hybrid composites for various industrial and domestic applications.